2014
DOI: 10.7124/bc.00089d
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of cell motility evaluation in scratch assay

Abstract: A scratch test is one of the most popular methods of classical cell migration assay in a monolayer culture. At the same time, the scratch assay has some disadvantages that can be easily corrected. Aim. Optimization the existent scratch assay on the base of detection of scratch wound surface area and the length of the field of observation which is more objective and less time consuming. Methods. Scratch assay. Results. The modification of scratch assay enables to perform measurement more accurately and rapidly.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…After the scratch was created, digitized images of a wound closure were taken at 0 h and 24 h with the Leica DM 1000 microscope and a digital camera. The average distance (µm) between the wound edges was determined at each time point as it was described in [26]. The scratch wound assay was performed in triplicates for each cell line used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…After the scratch was created, digitized images of a wound closure were taken at 0 h and 24 h with the Leica DM 1000 microscope and a digital camera. The average distance (µm) between the wound edges was determined at each time point as it was described in [26]. The scratch wound assay was performed in triplicates for each cell line used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…However, there are still some drawbacks of scratch assay that could not be avoided, including the inability to distinguish between the effect of proliferation and changes in cell survival, instability over period of 24 h, differing stain quality, leftover of cells, debris in the scratch area, accidental cell damage, floating apoptotic cells and uneven scratch [95,96]. Even so, as one of the traditional and classical methods, the scratch assay is firmly established as a popular and affordable method in studying cell migration in monolayer culture, while prevailing over other modern approaches such as the cell exclusion zone assay and radius 2D-cell migration assay [97]. Another better option is the use of 3D models like spheroid migration assay and capillary chamber migration assay, where cells can grow naturally and interact with each other, the ECM and microenvironment [98].…”
Section: Discussionmentioning
confidence: 99%
“…This test was developed to demonstrate how vegetable preparations or isolated compounds influence the formation of new cloth. [22,23] The results of this test are described in Figure 3. We found that the resin at concentrations of 0.001%, 0.0001%, and 0.00001% induced 3T3 fibroblast migration over a period of 24 h. The resin, at proteins in fibroblasts, including fibronectin, collagen, and hyaluronic acid, in addition to the synthesis of collagenases.…”
Section: Scratch Assaymentioning
confidence: 99%
“…), 205 (29), 204(22), 186(24), 184 (69), 169 (56), 161(23), 149 (100), 141 (37), 133 (28), 123 (39), 107 (35), 93 (37), 91 (41), 79 (34)Chiavari G. et al, + 320 (5), 192(15), 191 (100), 135(11), 212(8), 109(8), 105(7), 95(10), 91(8), 69 (9) + 320 (2), 192(14), 191 (100), 135(10), 121(7), 109 (7), Contd...…”
mentioning
confidence: 99%